A preliminary analysis of Key Issues in chemical industry accident reports. (February 2016) - Fyffe, Lyndsey; Krahn, Steven; Clarke, James; Kosson, David; Hutton, James
Highlights: An analysis is presented of Key Issues from accidents in the chemical industry. Key Issues are grouped to indicate accident themes in the chemical industry. Grouping of Key Issues is based on industry standards, such as OSHA PSM. Facilities, companies, or industry groups could use this information to improve process safety. Abstract: Chemical industry accident reports provide a wealth of information that can be used to develop lessons learned to improve safety and efficiency of operations at chemical industry facilities. The United States Chemical Safety Board (CSB) is one source of these accident reports. As a part of an investigation and causal analysis process, CSB investigators identify "Key Issues" for each chemical accident. This research evaluated trends in those Key Issues by applying two distinct analyses of these issues. The first analysis assessed the Key Issues naturalistically, as reported by the expert investigation team; however, this result was problematic, as about 2/3 of all Key Issues, as described in the chemical industry accident reports, occurred only once. In the second analysis, the Key Issues were sorted thematically to capture insights from the many single-occurrence issues. This thematic analysis, using categories drawn from the Occupational Safety and Health Administration's (OSHA's) Process Safety Management (PSM) guidance, allowed for a more comprehensive understanding and grouping of the issues behind the chemical accidents studied. The findings of this research identified several accident themes that can be used to develop a better understanding of chemical industry accidents and potentially improve safety and efficiency of operations at chemical facilities.